PAHs biodegradation potential of indigenous consortia from agricultural soil and contaminated soil in two-liquid-phase bioreactor (TLPB) - Wang, Congying; Wang, Fang; Wang, Tao; Bian, Yongrong; Yang, Xinglun; Jiang, Xin (Journal of hazardous materials, 2010)
Estimation of PAHs degradation potential of indigenous consortia is essential for remediation of polluted soils. In this study, the biodegradation of a mixture of 11 PAHs was compared using a long-term PAH-contaminated soil (CS) and an unpolluted agricultural soil (AS) as inocula in a two-liquid-phase bioreactor (TLPB). In the TLPB, silicone oil was used as the organic phase to increase the PAHs bioavailability. The microbial numbers were also determined during the biodegradation. The results demonstrated that naphthalene, fluorene, phenanthrene, anthracene, fluoranthene and pyrene could be completely biodegraded in both soils within 4–50 days. With the exception of dibenzo(a,h)anthrancene, the other PAHs including benzo(a)anthracene, benzo(a)pyrene, benzo(b)fluoranthene and benzo(k)fluoranthene were degraded to different extents in both soils at the end of 170 days. Complete biodegradation of benzo(a)anthracene and benzo(b)fluoranthene only occurred in CS. During the process, microbial growth was highly correlated to the biodegradation of PAHs. Sequential utilization of PAHs showed a competitive-inhibition in the multi-substrate system. The half-life times of PAHs obtained here were much shorter than those reported previously in soils, indicating that indigenous microbes in both soils had high PAHs degradation potential, facilitated by TLPB.